2020
DOI: 10.1186/s13073-020-00798-3
|View full text |Cite
|
Sign up to set email alerts
|

PathoSPOT genomic epidemiology reveals under-the-radar nosocomial outbreaks

Abstract: Background Whole-genome sequencing (WGS) is increasingly used to map the spread of bacterial and viral pathogens in nosocomial settings. A limiting factor for more widespread adoption of WGS for hospital infection prevention practices is the availability of standardized tools for genomic epidemiology. Methods We developed the Pathogen Sequencing Phylogenomic Outbreak Toolkit (PathoSPOT) to automate integration of genomic and medical record data for rapid detection and tracing of nosocomial outbreaks. To demon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In a multicenter study, 82% of patients with MRSA bacteremia had identical clones in the anterior nares, and 86% of patients with MRSA colonization in anterior nares had clonally identical isolates later obtained from blood [ 10 ]. Colonization is also key to subtle transmission events and has been a central feature of outbreaks [ 11 , 12 ]. In the United States, most S. aureus infections are caused by two dominant clonal complexes (CC), CC5 and CC8 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter study, 82% of patients with MRSA bacteremia had identical clones in the anterior nares, and 86% of patients with MRSA colonization in anterior nares had clonally identical isolates later obtained from blood [ 10 ]. Colonization is also key to subtle transmission events and has been a central feature of outbreaks [ 11 , 12 ]. In the United States, most S. aureus infections are caused by two dominant clonal complexes (CC), CC5 and CC8 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most US hospitals have not yet implemented a WGS surveillance system for infection control. Hospitals may choose to approach bioinformatic surveillance using commercial workflows with integrated processes [35], available open source options [38], or create robust in-house surveillance methods [39]. In this analysis we demonstrated that different methods of DNA sequence alignment can readily detect similar variation in SNP differences.…”
Section: Discussionmentioning
confidence: 91%
“…Two articles in this special issue illustrate the important role of genomics in understanding and controlling the burden of antimicrobial resistant infections in hospitals. Berbel Caban et al [19] present a method to facilitate the detection of inhospital spread of methicillin resistant Staphylococcus aureus (MRSA or "golden Staph") by combining genomic and epidemiological data. The genetics of antimicrobial resistance can be incredibly complex, and for most pathogens, the overall burden of resistant infections is the combined result of the spread of resistance genes and plasmids between bacterial strains and the transmission of bacterial strains between patients.…”
Section: Infectious Disease Genomics and Public Healthmentioning
confidence: 99%